The major impacts of change from cash to accrual accounting in the public sectors / Nik Zam Nik Wan - Nik Wan, Nik Zam (Universiti Teknologi MARA Cawangan Pahang, 2005)
Accrual accounting is seen as a solution to the problem faced by the traditional cash based accounting. This paper begins by describing cash based accounting and looks at its drawbacks that lead to the need for change. Then it explains the nature of accrual accounting and rationalises how accrual accounting system will benefit the public sectors. The paper continues further to review the implementation of accrual accounting in New Zealand and Australia as leading proponents of the adoption. The key issue of this paper is to review the major impacts of a change from cash to accrual accounting in the public sectors. The content of this discussion is based on various comments and views from various authors mostly from the countries that have been involved or will be involved in accrual accounting. The impacts are viewed from various angle such as the impact on financial reporting – presentation of balance sheet and problems associated, accounting profession, standard setting bodies, organisational culture – staff training and resistant, the need for efficient information system to support the system, the need for assets register to allow for recognition of assets. The paper looks at whether the advantages of accrual accounting can be realised by public sector accounting. The finding is that the change from cash to accrual accounting in the public sectors did have impacts on various parts as discussed in the paper. Some of the impacts give positive influences and some do not. But the presentation of this paper is not to deny the superiority of accrual accounting but hopefully be an eye-opener of the barriers associated so that any countries interested in the implementation of accrual accounting such as Malaysia will be aware and well prepared of such impacts. Nonetheless, the barriers, if overcome, can position countries in high standards.